Host factors facilitating SARS‐CoV‐2 virus infection and replication in the lungs - Boutin, Sébastien; Hildebrand, Dagmar; Boulant, Steeve; Kreuter, Michael; Rüter, Jule; Pallerla, Srinivas Reddy; Velavan, Thirumalaisamy P.; Nurjadi, Dennis (Cellular and molecular life sciences, 2021)
SARS-CoV-2 is the virus causing the major pandemic facing the world today. Although, SARS-CoV-2 primarily causes lung infection, a variety of symptoms have proven a systemic impact on the body. SARS-CoV-2 has spread in the community quickly infecting humans from all age, ethnicities and gender. However, fatal outcomes have been linked to specific host factors and co-morbidities such as age, hypertension, immuno-deficiencies, chronic lung diseases or metabolic disorders. A major shift in the microbiome of patients suffering of the coronavirus disease 2019 (COVID-19) have also been observed and is linked to a worst outcome of the disease. As many co-morbidities are already known to be associated with a dysbiosis of the microbiome such as hypertension, diabetes and metabolic disorders. Host factors and microbiome changes are believed to be involved as a network in the acquisition of the infection and the development of the diseases. We will review in detail in this manuscript, the immune response toward SARS-CoV-2 infection as well as the host factors involved in the facilitation and worsening of the infection. We will also address the impact of COVID-19 on the host’s microbiome and secondary infection which also worsen the disease.
Gesehen am 21.07.2023